Pengaruh Kompetensi Kepribadian Guru Terhadap Karakter Siswa di SMA Negeri 2 Kotamobagu Sulawesi Utara - Monalisa Torangan; Hasibuddin, Hasibuddin; Shamad, Ishak (Program Pascasarjana Universitas Muslim Indonesia, 2023)
This research was conducted with the aim of knowing whether there is an effect of the teacher's personality competence on student character. This research was conducted using a quantitative approach, namely descriptive correlational, namely looking for relationships and the influence of independent variables, Teacher Personality Competence (X) with the dependent variable Student Character (Y). Based on teacher personality competency data at SMA Negeri 2 Kotamobagu is in the very good category with a tendency of teacher personality competence of 92%, student character data at SMA Negeri 2 Kotamobagu is in the very good category with a student character tendency of 82%. There is an influence between the teacher's personality competence on student character with a relationship level of 0.136 or 13.6% while 86.4% is influenced by other factors, such as from within, family, community, and so on which can influence student character. Thus there is a significant influence between the Teacher Personality Competency variable (X) and the Student Character variable (Y).